2002
DOI: 10.1006/dbio.2001.0424
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mosaic Analysis Reveals That GATA-4 Is Required for Proper Differentiation of Mouse Gastric Epithelium

Abstract: During mouse embryogenesis GATA-4 is expressed first in primitive endoderm and then in definitive endoderm derivatives, including glandular stomach and intestine. To explore the role of GATA-4 in specification of definitive gastric endoderm, we generated chimeric mice by introducing Gata4(-/-) ES cells into ROSA26 morulae or blastocysts. In E14.5 chimeras, Gata4(-/-) cells were represented in endoderm lining the proximal and distal stomach. These cells expressed early cytodifferentiation markers, including GAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 77 publications
8
82
0
Order By: Relevance
“…2E,F,I,J). This altered expression pattern of Shh in Gata4 ki/ki mice mirrored that reported in Gata4 -/-chimeric mice (Jacobsen et al, 2002), suggesting that a GATA-4: FOG interaction lies downstream of activin receptor-mediated signals and serves to attenuate Shh expression in the developing hindstomach.…”
Section: Resultssupporting
confidence: 71%
See 4 more Smart Citations
“…2E,F,I,J). This altered expression pattern of Shh in Gata4 ki/ki mice mirrored that reported in Gata4 -/-chimeric mice (Jacobsen et al, 2002), suggesting that a GATA-4: FOG interaction lies downstream of activin receptor-mediated signals and serves to attenuate Shh expression in the developing hindstomach.…”
Section: Resultssupporting
confidence: 71%
“…Previous studies have shown that GATA-4 is expressed in hindstomach epithelial cells throughout fetal and postnatal development and localizes in pit, neck, and parietal cells in the mature glandular epithelium (Jacobsen et al, 2002;Nemer and Nemer, 2003). FOG-1 expression has been documented in hematopoietic progenitors, gonadal cells, and the heart (Tsang et al, 1997;Tevosian et al, 2002;Katz et al, 2003;Gitler et al, 2003), while FOG-2 has been detected in brain, gonadal somatic cells, and cardiac tissue (Tsang et al, 1997(Tsang et al, , 1998Svensson et al, 1999;Tevosian et al, 1999;Lu et al, 1999;Anttonen et al, 2003).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations